Optimising Decentralisation for the Health Sector by Exploring the Synergy of Decision Space, Capacity and Accountability: Insights From the Philippines - Liwanag, Harvy Joy (Archīum Ateneo, 2019)
Background Several studies on decentralisation have used the ‘decision space’ approach to assess the breadth of space made available to decision-makers at lower levels of the health system. However, in order to better understand how decentralisation becomes effective for the health sector, analysis should go beyond assessing decision space and include the dimensions of capacity and accountability. Building on Bossert’s earlier work on the synergy of these dimensions, we analysed decision-making in the Philippines where governmental health services have been devolved to local governments since 1992. Methods Using a qualitative research design, we interviewed 27 key decision-makers at different levels of the Philippine health system and representing various local settings. We explored their perspectives on decision space, capacities and accountability in the health sector functions of planning, financing and budget allocation, programme implementation and service delivery, management of facilities, equipment and supplies, health workforce management, and data monitoring and utilisation. Analysis followed the Framework Method. Results Across all functions, decision space for local decision-makers was assessed to be moderate or narrow despite 25 years of devolution. To improve decision-making in these functions, adjustments in local capacities should include, at the individual level, skills for strategic planning, management, priority-setting, evidence-informed policy-making and innovation in service delivery. At institutional levels, these desired capacities should include having a multi-stakeholder approach, generating revenues from local sources, partnering with the private sector and facilitating cooperation between local health facilities. On the other hand, adjustments in accountability should focus on the various mechanisms that can be enforced by the central level, not only to build the desired capacities and augment the inadequacies at local levels, but also to incentivise success and regulate failure by the local governments in performing the functions transferred to them. Conclusion To optimise decentralisation for the health sector, widening decision spaces for local decision-makers must be accompanied by the corresponding adjustments in capacities and accountability for promoting good decision-making at lower levels in the decentralised functions. Analysing the health system through the lens of this synergy is useful for exploring concrete policy adjustments in the Philippines as well as in other settings.